Effect of reciprocating file motion on microcrack formation in root canals: an SEM study. (24th October 2013) - Ashwinkumar, V.; Krithikadatta, J.; Surendran, S.; Velmurugan, N.
Abstract Aim To compare dentinal microcrack formation whilst using Ni–Ti hand K‐files, ProTaper hand and rotary files and the WaveOne reciprocating file. Methodology One hundred and fifty mandibular first molars were selected. Thirty teeth were left unprepared and served as controls, and the remaining 120 teeth were divided into four groups. Ni–Ti hand K‐files, ProTaper hand files, ProTaper rotary files and WaveOne Primary reciprocating files were used to prepare the mesial canals. Roots were then sectioned 3, 6 and 9 mm from the apex, and the cut surface was observed under scanning electron microscope (SEM) and checked for the presence of dentinal microcracks. Results The control and Ni–Ti hand K‐files groups were not associated with microcracks. In roots prepared with ProTaper hand files, ProTaper rotary files and WaveOne Primary reciprocating files, dentinal microcracks were present. There was a significant difference between control/Ni–Ti hand K‐files group and ProTaper hand files/ProTaper rotary files/WaveOne Primary reciprocating file group (P < 0.001) with ProTaper rotary files producing the most microcracks. No significant difference was observed between teeth prepared with ProTaper hand files and WaveOne Primary reciprocating files. Conclusion ProTaper rotary files were associated with significantly more microcracks than ProTaper hand files and WaveOne Primary reciprocating files. Ni–Ti hand K‐files did not produce microcracks at any levels inside the root canals.